Analisis kemampuan berbicara peserta didik kelas vb dalam pembelajaran bahasa indonesia semester genap di sekolah dasar - Destiana Endika Pratiwi; Septi Yulisetiani (Universitas Sebelas Maret, 2025)
This study aims to analyze the speaking ability of grade VB students in learning Indonesian in the even semester at SDN Kemasan 1 Surakarta. Using a qualitative case study approach, the research focuses on three main aspects: students' speaking proficiency, linguistic and non-linguistic influencing factors, and challenges in improving speaking skills. Data were collected through passive observation, structured interviews with teachers and students, and document analysis. The results indicate that most students demonstrate strong mastery of linguistic aspects (intonation, articulation, sentence structure, content accuracy, and vocabulary selection) and non-linguistic aspects (fluency, facial expressions, volume, confidence, and body gestures) in delivering speeches, advertisements, explanatory texts, and rhymes. However, some students face challenges such as nervousness, limited vocabulary, and inconsistent sentence structure. The study emphasizes the importance of structured practice, teacher feedback, and a supportive learning environment to enhance speaking skills. Practical recommendations include interactive learning methods and confidence-building activities. The findings provide guidance for educators in designing strategies to develop students' speaking abilities.